2013
DOI: 10.1007/s13105-013-0239-6
|View full text |Cite
|
Sign up to set email alerts
|

Basal leptin regulates amino acid uptake in polarized Caco-2 cells

Abstract: Leptin is secreted by gastric mucosa and is able to reach the intestinal lumen where its receptors are located in the apical membrane of the enterocytes. We have previously demonstrated that apical leptin inhibits sugar and amino acids uptake in vitro and glucose absorption in vivo. Since leptin receptors are also expressed in the basolateral membrane of the enterocytes, the aim of the present work was to investigate whether leptin acting from the basolateral side could also regulate amino acid uptake. Tritiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To further elucidate the function of receptors in each stage of NP transport, the hormone leptin was used. Leptin receptors are present all along the intestine within the brush border, and leptin can regulate expression of various transporters and the absorption of nutrients. , According to previous reports, leptin also affected free butyrate absorption and regulated MCT-1 expression. , Here, after preincubation with leptin for 18 h, cells were exposed to both NPs. It was found that only Bu-PEG NPs showed greatly reduced internalization (only ∼40% of control group) at the concentration of leptin ranging from 1 to 200 nM (Figures B and S3A).…”
Section: Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…To further elucidate the function of receptors in each stage of NP transport, the hormone leptin was used. Leptin receptors are present all along the intestine within the brush border, and leptin can regulate expression of various transporters and the absorption of nutrients. , According to previous reports, leptin also affected free butyrate absorption and regulated MCT-1 expression. , Here, after preincubation with leptin for 18 h, cells were exposed to both NPs. It was found that only Bu-PEG NPs showed greatly reduced internalization (only ∼40% of control group) at the concentration of leptin ranging from 1 to 200 nM (Figures B and S3A).…”
Section: Results and Discussionmentioning
confidence: 76%
“…Leptin receptors are present all along the intestine within the brush border, and leptin can regulate expression of various transporters and the absorption of nutrients. 27,28 According to previous reports, leptin also affected free butyrate absorption and regulated MCT-1 expression. 29,30 Here, after preincubation with leptin for 18 h, cells were exposed to both NPs.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 81%
“…By contrast, amino acids may be distributed more heterogeneously, since they enter cell cytoplasm and participate in cell metabolic processes. For example, the intestinal epithelium, and especially the basal part of the villi where amino acids are absorbed by enterocytes 50 , may concentrate TAA before transport into the blood. Moreover, the AAs are absorbed mainly by the duodenum and the upper part of the jejunum 42 .…”
Section: Discussionmentioning
confidence: 99%